Formulation Development and Evaluation of Self-nanoemulsifying Drug Delivery System of Vitamin A for Better Bioavailability - Farooq, Syed Umar (Asian Journal of Pharmaceutics (AJP), 2019)
Aims: The objective of the investigation is to formulate self-nanoemulsifying drug delivery system (SNEDDS) of Vitamin A (tocopherol) to improve its aqueous solubility as its fat-soluble vitamin. Settings, Design, Methodology: Solubility of Vitamin A in various oil surfactants and cosurfactants is determined. Ternary phase diagram is constructed at different ratios of surfactant and co-surfactants to determine self-emulsifying region. Effect of oil content, pH of aqueous phase and mean globule size of resulting nanoemulsion is studied. Optimized formulation was identified and was evaluated for in vitro dissolution profile in comparison with pure drug. Results: Self-emulsifying drug delivery systems yielded nanoemulsion with globule size range of 81.7 nm with the Z average of 504.4 nm indicating all the particles were in nano-meter range. Drug content was measured and found to be 99.62% in optimized formulation A20. Phase inversion is not noticed after thermodynamic studies. Conclusion: SNEDDS of Vitamin A comprising of clove oil, Tween 40, and polyethylene glycol 600 were prepared for enhancing the dissolution and bioavailability. SNEDDS were optimized based on the optimum globule size, increased dissolution, and drug release. Close to complete drug release was achieved from the formulation A20 which is significantly higher as compared to that of other formulations.